PENGELOLAAN BARANG MILIK NEGARA DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK (FISIP) UNIVERSITAS RIAU - Willian Sandra; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to explain how the Management of State Property at the Faculty of Social and Political Sciences, University of Riau. Based on the phenomenon found in the field, there are some obstacles in the management of the State Property, such as the goods are not found as evidence of damage or badly damaged assets, mobile assets that move from its place like A building seats move to building B causing incompatibility of recorded inventory data , A complicated and time-consuming procedure for removing State Property.In this study the authors use the theory (Siregar 2004 : 518-520) regarding asset management ie Asset Inventory, Legal Audit, Asset Rating, Asset Optimization, Supervision and Control. As a reference in the management of State Property at the Faculty of Social and Political Sciences, University of Riau.Based on these aspects the authors hold that the State Property Management in the Faculty of Social and Political Sciences of the University of Riau has performed its duties based on Standard Operating Procedures (SOP) that exist. In order to realize the good State Property Management at the Faculty of Social and Political Sciences, University of Riau.Keywords: Management, State Property, Faculty of Social and Political Sciences